PERSONALIZED COGNITIVE COUNSELING IN PREVENTING RISK BEHAVIOR AMONG MEN WHO HAVE SEX WITH MEN (MSM): A LITERATURE REVIEW - Lussy Afriyanti; Agung Waluyo (International Journal of Nursing and Health Services (IJNHS), 2019)
The current trend of HIV infection shows an increase in cases among men who have sex with men (MSM). Risk behavior in MSM has shown a high prevalence of moderate and worrying risk behaviors for HIV infection, including unprotected anal intercourse (UAI) and drug use. This literature review aims to explore the effectiveness of Personalized Cognitive Counseling (PCC) interventions in reducing risk behaviors for HIV transmission to MSM. Articles discussed in this literature study were obtained from several databases using the keywords “personalized cognitive counseling," “men who have sex with men," and "risk behavior." Cognitive counseling interventions are effective in reducing episodes of anal intercourse. Adapted Personalized Cognitive Counseling (PCC) intervention also has been effective in reducing sexual risk behavior in drug users MSM. This intervention is possible and essential to developing in dealing with risk behavior in MSM that tends to increase in its population. Keywords: cognitive counseling, personalized cognitive counseling, men who have sex with men (MSM), risk behavior